Side-lobe reduction in pulse compression having a better range resolution. (March 2019) - Thakur, Ankur; Talluri, Salman Raju; Panigrahi, Rajib Kumar
Abstract: This paper shall portray a technique for the reduction of side-lobe levels in the pulse compression (PC) for a radar system. PC is used in radar systems to improve the range resolution of the targets specifically in high resolution radar systems in which the system has to distinguish between two nearby targets as distinct. The proposed PC technique has been carried out by shifting input P4 code and by multiplying it with reference signal in frequency domain. Thereafter, side-lobe behavior is analyzed in time domain. P4 code belongs to the class of polyphase codes which is more Doppler tolerant. Ambiguity function (AF) of the proposed waveform is mathematically derived and its capability for range resolution and clutter suppression is observed by simulations. Results indicate that the proposed method produces less side-lobe levels and better range resolution than linear frequency modulated (LFM) and other polyphase codes. All of the aforesaid methods are carried out with the aid of mathematical equations and its effectiveness has been tested by using simulation verifications